PELATIHAN PERTANIAN ORGANIK BAGI PETANI DI DESA WARI INO KECAMATAN TOBELO - Hunila, Ernny; Popoko, Stefen; Payer, Dony (HIRONO : Jurnal Pengabdian Masyarakat, 2023)
The purpose of this community service activity is to improve the knowledge and skills of farmers in terms of organic farming, composting and liquid organic fertilizer. This activity was carried out in Wari Ino Village, Tobelo District, North Halmahera Regency, lasting for 5 days with participants being a number of Wari Ino Village farmers who live in circle of the Campus of Polytechnic Perdamaian Halmahera. Activities are divided into preparation, counseling, training activities and making vegetable crop plots and conducting evaluations.  The results of the evaluation of the implementation of organic agricultural extension and training in making composters and liquid organic fertilizers show that there is an increase in farmers' knowledge and skills.